2021
DOI: 10.1111/his.14435
|View full text |Cite
|
Sign up to set email alerts
|

PD‐L1 expression and immune stromal features in HPV‐independent cervical adenocarcinoma

Abstract: Human papilloma virus (HPV)-independent cervical adenocarcinoma (CA) is usually diagnosed at an advanced stage, while the therapeutic options are limited. Therefore, effective treatment options are required. The programmed cell death 1 (PD-1) inhibitor pembrolizumab has been approved for the treatment of patients with recurrent or metastatic cervical squamous cell carcinoma expressing PD-ligand 1 (PD-L1). However, no data regarding PD-L1 expression in HPV-independent CA are available. Thus, we evaluated the as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 34 publications
(44 reference statements)
1
8
0
Order By: Relevance
“…Some research has suggested that the prognosis of each AC varies according to its histopathological type ( 12 , 22 , 28 - 30 ). Some investigators have suggested that different subtypes of cervical AC may be different at the molecular level ( 31 , 32 ), Taken as a whole, from a clinical point of view, our results suggest that EC may be associated with better survival than AC even after PSM. However, these results need to be confirmed in prospective studies with large-sample sizes.…”
Section: Discussionsupporting
confidence: 60%
“…Some research has suggested that the prognosis of each AC varies according to its histopathological type ( 12 , 22 , 28 - 30 ). Some investigators have suggested that different subtypes of cervical AC may be different at the molecular level ( 31 , 32 ), Taken as a whole, from a clinical point of view, our results suggest that EC may be associated with better survival than AC even after PSM. However, these results need to be confirmed in prospective studies with large-sample sizes.…”
Section: Discussionsupporting
confidence: 60%
“…Studies about PDL1 expression in NHPVA are limited. Recently, Song and Chen investigated PDL1 expression among different histotypes of NHPVA and its correlation with prognosis, progression-free survival, and overall survival [ 107 , 108 ].…”
Section: Molecular Characterization Of Non-hpv Associated Adenocarcinomamentioning
confidence: 99%
“…CPS is defined as the number of PDL1 stained cells (tumor cells, lymphocytes, and macrophages) divided by the total number of viable tumor cells and then multiplied by 100. TPS is the percentage of viable tumor cells showing partial or complete membrane staining adenocarcinoma positive or PDL1 expression [ 107 , 108 ].…”
Section: Molecular Characterization Of Non-hpv Associated Adenocarcinomamentioning
confidence: 99%
See 2 more Smart Citations